2016
DOI: 10.1038/srep29648
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for insulin-like peptide 5 distinguishing the homologous relaxin family peptide receptor 3 and 4

Abstract: The relaxin family peptides play a variety of biological functions by activating four G protein-coupled receptors, RXFP1–4. Among them, insulin-like peptide 5 (INSL5) and relaxin-3 share the highest sequence homology, but they have distinct receptor preference: INSL5 can activate RXFP4 only, while relaxin-3 can activate RXFP3, RXFP4, and RXFP1. Previous studies suggest that the A-chain is responsible for their different selectivity for RXFP1. However, the mechanism by which INSL5 distinguishes the homologous R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…R B12 in the B-chain of ΔR3/I5 was previously reported to be one of the residues important for binding to both RXFP3 and RXFP4 16 . The corresponding residue L B9 in the B-chain of INSL5, on the other hand, was reported to be one of the most critical residues by which INSL5 exhibits selectivity for RXFP4 over RXFP3 27 . Therefore, in the first attempt, we replaced the R B12 residues in the B-chain of ΔR3/I5 with corresponding L B9 residue of INSL5 B-chain in order to achieve selectivity for RXFP4 over RXFP3 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…R B12 in the B-chain of ΔR3/I5 was previously reported to be one of the residues important for binding to both RXFP3 and RXFP4 16 . The corresponding residue L B9 in the B-chain of INSL5, on the other hand, was reported to be one of the most critical residues by which INSL5 exhibits selectivity for RXFP4 over RXFP3 27 . Therefore, in the first attempt, we replaced the R B12 residues in the B-chain of ΔR3/I5 with corresponding L B9 residue of INSL5 B-chain in order to achieve selectivity for RXFP4 over RXFP3 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…3D) compared with ΔR3/I5. The fact that the agonist peptide R3/I5 with the same mutation (R B12 /L B9 ) was shown to exhibit ~1600 less RXFP3 potency without losing much RXFP4 potency 27 suggest that the binding mode of the agonist (R3/I5) peptide for RXFP3 and RXFP4 might be different to that of the antagonist peptide (ΔR3/I5).
Figure 3Competition binding curves for ΔR3/I5 and novel chimeric analogues 14–20 , ( A – C ) in comparison to Eu-B1-22R in RXFP3-expressing cells and ( D – F ) in comparison to Eu-INSL5 in RXFP4-expressing cells. The data are the result of n = 3–4 independent experiments and are expressed as mean ± SEM.
…”
Section: Resultsmentioning
confidence: 99%
“…While H3 relaxin cross‐reacts with other receptors including RXFP4 receptors, INSL5 is very selective (RXFP4) and does not interact with RXFP3 receptors. The mechanism by which INSL5 distinguishes RXFP4 and RXFP3 receptors has recently been identified (Hu et al, ). The authors have identified four determinants (E B2 , L B9 , Y B17 and a rigid B‐chain C‐terminus) on INSL5 that are responsible for its inactivity at RXFP3 receptors (Hu et al, ).…”
Section: Human Insl5mentioning
confidence: 99%
“…Among them, RXFP4 and its endogenous ligand INSL5 have been linked to insulin secretion and appetite [ 8 , 11 ], thereby making them a potential therapeutic target for obesity and other metabolic disorders. Given the complexity of the interaction between RXFP4 and INSL5 [ 23 ], it is not surprising that the number of ligands selective for the receptor is rather limited. It is also well recognized that the synthesis of INSL5 and its peptide analogs is technically challenging [ 13 , 14 ], and nonpeptidic agonists are thus in high demand.…”
Section: Discussionmentioning
confidence: 99%